Penggunaan Model Cooperative Learning Tipe Numbered Head Together (NHT) untuk meningkatkan Hasil Belajar IPS di Kelas IV SDN 07 Silaut Kecamatan Silaut Kabupaten Pesisir Selatan - Tugiman Tugiman (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This type of research is classroom action research. This study uses a qualitative approach, including 1) planning, 2) implementation, 3) observation, and 4) reflection. Subjects in this study were students of grade IV elementary school which amounted to 30 people. The research results of the first cycle of the pre-learning test average score of 5.94 students and in the final test student learning completeness reached 56.7%, while the final test of the second cycle the value of student learning completeness increased to 80%. Based on the observations, it was seen that the students 'understanding was improved after the learning process took place which was reflected in the students' test results. It can be concluded that learning using the Cooperative Learning Model Type NHT can improve student learning outcomes in the material of economic activities related to natural resources and other potential in the region (West Sumatra).